Investigation of the effect of 6-week yoga exercises on balance, flexibility, and strength in soccer players - Kartal, A.; Ergin, E. (International Journal of Human Movement and Sports Sciences, 2020)
The aim of this study was to investigate the effect of 6-week yoga exercises on balance, flexibility, strength, and body fat percentage in soccer players. The sample group of the study consisted of 26 soccer players in a team, competing in the Turkish 1st League, with a mean height of 180.81 ± 6.87 centimeters (cm), mean body weight of 75.77 ± 9.08 kilograms (kg), and a body mass index (BMI) of 23.10 ± 1.62. Basic-level strength yoga exercise techniques were applied to soccer players for 6 weeks, 4 times a week each for 30 minutes before morning soccer training. The participants' balance, flexibility, and strength measurements were carried out twice, before and after 6-week yoga exercises. An Easytech dynamic balance system was used for balance measurements, a Takei-branded handgrip measuring device was used for strength measurements, and the sit and reach flexibility test was used for flexibility measurements. The data obtained from the study were analyzed using SPSS (Statistical Package for Social Sciences) for Windows 25.0. Descriptive statistical methods (number, percentage, mean, and standard deviation) were used in the evaluation of the data. The paired t-test, which is one of the parametric tests, was applied for the normally distributed parameters. According to the results of statistical analysis, a significant difference was found in the pre-test and post-test balance, flexibility and strength measurements of the participants (p0.05). In conclusion, it can be said that 6-week basic-level strength yoga exercises had a positive effect on balance, flexibility, and strength in soccer players. Furthermore, it may be suggested that yoga exercises to be applied by coaches before the season should be included in training programs considering that they will contribute to the motor development of soccer players.